Differential Apoptotic Responses of Hemocyte Subpopulations to White Spot Syndrome Virus Infection in Fenneropenaeus chinensis - Cui, Chuang; Liang, Qianrong; Tang, Xiaoqian; Xing, Jing; Sheng, Xiuzhen; Zhan, Wenbin (Frontiers in Immunology, 2020)
The apoptosis of hemocytes plays an essential function in shrimp immune defense against pathogen invasions. In order to further elucidate the differential apoptotic responses of the granulocytes and the hyalinocytes in Fenneropenaeus chinensis post WSSV infection, the characteristics of apoptotic dynamics and viral proliferation in total hemocytes and hemocyte subpopulations were respectively investigated in the present work. The results showed that the apoptotic rate of hemocytes changed significantly, and the apoptosis-related genes also showed significantly differential expression responses during WSSV infection. Interestingly, we found that the apoptotic rate of virus-negative hemocytes was significantly higher than that of virus-positive hemocytes in the early stage of WSSV infection, while it was significantly lower than that of virus-positive cells in the middle and late infection stages. The difference of apoptosis between virus-positive and virus-negative hemocytes seems to be an important way for the WSSV to destroy the host’s immune system and facilitate the virus spread at different infection stages. It was further found that the apoptosis rate of granulocytes was always significantly higher than that of hyalinocytes during WSSV infection, indicating that granulocytes have a stronger apoptotic response to WSSV infection. Moreover, a higher viral load was detected in granulocytes, and the density of granulocytes decreased more rapidly post WSSV infection, indicating that the granulocytes are more susceptible and vulnerable to WSSV infection compared with the hyalinocytes. These results collectively demonstrated that the apoptotic response in shrimp hemocytes was significantly influenced by the WSSV infection, and the differential apoptotic response of granulocytes and hyalinocytes to WSSV indicated the differences of antiviral mechanisms between the two hemocyte subpopulations.